Fool’s gold?: Sino-British elites and the ‘Golden Era’ of relations - Thorley, Martin (2021)
Fool’s Gold?: Sino-British Elites and the ‘Golden Era’ of Relations, employs an investigative research approach and novel elite theory framework to investigate elite level relations between the People’s Republic of China (PRC) and the United Kingdom (UK) in the 2010s. The study employs exploratory and experimental data gathering and data generation strategies. These include open source intelligence methods, extensive Freedom of Information requests and challenges, as well as Chinese and English language dual search source comparisons. The study examines the British decision to allow PRC involvement in its civil nuclear energy programme; PRC-UK cooperation in the City of London around renminbi internationalisation; and the hitherto under-investigated acquisitions of ultra-high value properties in London by PRC-linked entities and individuals. All three cases feature revelatory findings including apparent targeting by the party-state of senior British political figures and the creation of an All Party Parliamentary Group, ostensibly promoting Chinese party-state interests inside Parliament. By uncovering elite linkages not only within the three case studies but also between them, the thesis sheds light on previously obscure coordination of party-state activities and strategies abroad. The thesis also presents substantial evidence that party-state activity is particularly successful when utilising pre-existing channels forged by international commercial and financial interests to influence British politics. The thesis finds that, according to the elite theory framework it employs, the relationship between PRC and UK elites during the 2010s is best considered one of antagonistic cooperation. The thesis includes proposals that the UK (and comparable liberal democracies) could employ to reduce the efficacy of party-state operations. It also includes a discussion of the hitherto little understood role of financialisation and capitalisation in the post-Cold War West as factors in Western incapacity to repel party-state intrusion.